Improving Students' Geometric Thinking Levels through a Van Hiele Learning Module Integrated with Ethnomathematics - Arman Ramadan; Muhammad Ammar Naufal; Nur Wahidin Ashari; Muhammad Nasiru Hassan (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Analytic geometry learning often emphasizes symbolic procedures, while students’ spatial visualization and geometric reasoning remain underdeveloped. This gap highlights the urgency of developing culturally contextualized learning materials that connect concrete spatial experiences with formal mathematical concepts. This study aims to develop and evaluate the effectiveness of a local wisdom-based analytic geometry module in improving students’ geometric thinking levels (GTL). The study employed Research and Development (R&D) using the ADDIE framework, comprising Analysis, Design, Development, Implementation, and Evaluation. Participants were 36 third-semester pre-service mathematics teachers at Universitas Negeri Makassar, selected purposively. Data were collected through module validation sheets, student response questionnaires, and a seven-item open-ended Geometric Thinking Test, and analyzed descriptively and using the Wilcoxon Signed-Rank Test. The module achieved high validity based on subject matter (0.92) and cultural (0.80) expert validation and high practicality (83.79%). Wilcoxon analysis indicated a significant improvement in GTL (Z = −5.233; p < 0.001). Students reaching Level 3 (Formal Deduction) increased from 0% to 69.4%, while 2.8% reached Level 4 (Rigor). Integrating traditional-house wireframes and weaving patterns provided visual-cultural scaffolding that bridged spatial intuition and formal algebraic reasoning. These findings demonstrate the module’s potential to strengthen formal geometric reasoning and support culturally responsive mathematics education. Future studies should examine its effectiveness using larger, diverse samples and comparative designs.